Statistical calibration of two-dimensional seismic aggravation effects for homogeneous basins. Issue 163 (December 2022) - Uzielli, Marco; Facciorusso, Johann; Madiai, Claudia
Abstract: Two-dimensional basin effects often play a relevant role in defining earthquake ground motion at sites with deep morphologies. The quantitative estimation of two-dimensional effects requires a numerical approach which is typically complex and computationally demanding. Due to modelling complexities, basin effects are not routinely accounted for and have not received significant attention in seismic design codes. One-dimensional seismic response can be modeled with greater ease but does not allow their confident investigation. The use of simplified approaches which allow the estimation of two-dimensional effects from one-dimensional analyses is thus warranted. Past studies have defined and investigated aggravation factors, which can be applied as multiplicative coefficients to one-dimensional ground response outputs to account for two-dimensional basin effects. This paper proposes a novel framework for estimating basin effects by assigning aggravation factors for a vast range of symmetric basins overlain by a single-layer, homogeneous soil deposit and for varying basin sizes, dynamic geotechnical properties, and seismic inputs. In the study, aggravation factors are defined with reference to pseudo-acceleration response spectrum (5% of critical damping) and are calibrated statistically using a large set of dimensionless parameters from the outputs of an extensive set of one-dimensional and two-dimensional numerical analyses. The calibration process is described along with notable observations regarding the spatial variability of the magnitude of two-dimensional aggravation along the surface of the deposit. The proposed method is amenable to current design code formats involving tabulated partial factors. In principle, aggravation factors obtained in this study can be applied to 1D response spectra developed either from the provisions of the design codes themselves or from site-specific ground response analyses. A discussion focusing on the validation of the proposed approach using experimental and empirical measurements is provided. An example application attests to the simplicity of use of the method. Highlights: 1D ground response analyses often underestimate site effects in basins. 2D effects are due to geometric and geotechnical properties of basins. 2D effects can be parameterized through aggravation factors. 2D aggravation factors are spatially variable. 2D aggravation factors can be calibrated statistically in design code format. 2D aggravation factors can be applied to 1D response analysis or code-based spectra.